2005
DOI: 10.1177/1090198104272251
|View full text |Cite
|
Sign up to set email alerts
|

Organ Donor Registration Preferences Among Hispanic Populations: Which Modes of Registration Have the Greatest Promise?

Abstract: There is little debate over Hispanics' need for viable organs. Although organ donor registries can potentially assist in alleviating this need, the U.S. Department of Health and Human Services (DHHS) has called on researchers to investigate methods to maximize such potential. This research effort answers the aforementioned call by surveying Hispanics, both those who prefer to use Spanish (SP, n=239) and those who prefer not to use Spanish (NSP, n=364) about the methods of donor registration that they would mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 17 publications
2
37
0
Order By: Relevance
“…Hispanic American individuals accounted for nearly half of the national population growth between 2000 and 20043 and it is estimated that they will constitute one-third of the American population by the end of this century 4. As expected, this population growth parallels a growth in transplant organ need.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Hispanic American individuals accounted for nearly half of the national population growth between 2000 and 20043 and it is estimated that they will constitute one-third of the American population by the end of this century 4. As expected, this population growth parallels a growth in transplant organ need.…”
mentioning
confidence: 76%
“…We found that only 31% of the population expressed willingness to become an organ donor. This is far below the 46% intent to register seen in other Hispanic American communities, reinforcing the notion that Hispanic American individuals are not a homogeneous group and different communities may require different interventions 10. We found that independent contributing factors for the intent to become an organ donor included low acculturation, religion, belief that organ donation will disfigure the body and impact the funeral, perception that wealthy people are likely to receive organ transplants, family influence, and awareness of driver license registry.…”
Section: Commentmentioning
confidence: 89%
See 1 more Smart Citation
“…Low registration rates in specific immigrant groups may be influenced by many factors, including knowledge, attitude and awareness of organ donation, that were not measured in our study. The low registration rates may also have been due to unawareness of the registry 7,8 or fear of placing one's name in a large database 26 rather than a negative attitude toward organ donation. Second, Immigration, Refugees and Citizenship Canada's Permanent Resident Database contains only data recorded at the time of immigration.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…3 A national organ shortage at crisis proportion requires attention to this gap to increase the number of registered donors. A large presence on the waiting list matched with a historic lack of intent to donate makes the Hispanic American community a prime population on whom to focus resources and educational efforts to increase the number of registered donors.…”
Section: Discussionmentioning
confidence: 99%